Motivasi Intrinsik, Motivasi Ekstrinsik dan Disiplin Kerja Pengaruhnya terhadap Kinerja Pegawai pada Kantor Dinas Pendidikan Kabupaten Sambas - Nur Ida Iriani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research basicly aims to know the influence of motivation (intrinsic and extrinsic) and work discipline to employee performance. The location is chosen for this research is education officional office of Kabupaten Sambas. The research was done to 37 responden by using quantitative-explanatory approach. Thus, data analysis which is used is statistic analysis in the form of double linier regression test. The result of this research shows that either simultaneously or partially, the variable of intrinsic motivation, ekstrinsic motivation and work discipline influence work performance of the employee at officional office of education of Kabupaten Sambas. It has been proven from the result of (f) simultan test which shows confer (38,773) with significant point (0.000) which is much smaller than alpha 0.05. Along with the result of (t) partial shows significant point of three free variables in succession as big as 0.000, 0.009 and 0.000 which is much smaller than alpha 0.05. so that the accepted assumption from both of the test is Ho rejected.Keywords: intrinsic motivation, extrinsic motivation, work discipline, and employee performance